1988
DOI: 10.1021/ac00170a016
|View full text |Cite
|
Sign up to set email alerts
|

Laser-enhanced ionization as a selective detector for the liquid chromatographic determination of alkyltins in sediment

Abstract: 6, 11), led to variable recoveries and low values for most elements (Table IV). Hydrofluoric acid has been used for the dissolution of geologic samples (6). There has also been a report of HF use with some biological samples, particularly when silicon analyses are needed (3). However, when HF was added to our system, unacceptable amounts of particulate matter remained after digestion of the fecal samples; there were poor recoveries of most elements except for phosphorous and zinc. Digestions seemed to be more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…The theoretical basis for the high sensitivity and selectivity of LEAFS has been reviewed by Falk (7), Omenetto (8), and Alkemade (9). Recently, lasers have been employed as part of a detection system in the HPLC-laser-enhanced ionization (HPLC-LEI) detection of organotin compounds in a flame atom cell (10). In the work presented here, we report the use of high-performance liquid chromatography-ultraviolet (HPLC-UV), HPLCcontinuum source excited flame atomic fluorescence spectrometry (HPLC-AFC), and HPLC-flame laser-excited atomic fluorescence spectrometry (HPLC-flame LEAFS) instrumentation for the separation and quantitation of toxic organomanganese species.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The theoretical basis for the high sensitivity and selectivity of LEAFS has been reviewed by Falk (7), Omenetto (8), and Alkemade (9). Recently, lasers have been employed as part of a detection system in the HPLC-laser-enhanced ionization (HPLC-LEI) detection of organotin compounds in a flame atom cell (10). In the work presented here, we report the use of high-performance liquid chromatography-ultraviolet (HPLC-UV), HPLCcontinuum source excited flame atomic fluorescence spectrometry (HPLC-AFC), and HPLC-flame laser-excited atomic fluorescence spectrometry (HPLC-flame LEAFS) instrumentation for the separation and quantitation of toxic organomanganese species.…”
mentioning
confidence: 99%
“…Several HPLC interfaces have been reported for the determination of tributyl-and other alkyltin compounds. The following systems have been used for alkyltin determinations: HPLC-flame AAS with a detection limit of 10-20 ng of Sn (20); HPLC-DCP, for which no detection limit data have been reported ( 21); HPLC-GFAAS with a detection limit of 0.5 ng of Sn (22); HPLC-flame LEI with a detection limit of 60 pg of Sn (10); and HPLC hydride generation with a detection limit of 8-14 pg of Sn (20). Jewett and Brinckman (23) and Ebdon et al (24) reported that a strong cation-exchange HPLC column, used in conjunction with an ammonium acetate buffered eluent, provided satisfactory sepEiration of a wide variety of alkyltin species.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…21 The LEI technique can also be interfaced to ¯ow injection to reduce matrix interference effects 22,23 and serve as a chromatographic detector. 24,25 As reported previously, by measuring ion mobility and diffusion coef® cients of a thermometric species, one may determine the ¯ame temperature on the basis of the Einstein relation. 20 The advantage of the LEI method lies in its capabilities of achieving high spatial resolution and avoiding optical interference from scattered radiation and ¯ame background radiation.…”
Section: Introductionmentioning
confidence: 93%